The National SOM Survey 2008 - SOM Institute, University of Gothenburg (University of Gothenburg, 2011)
Since 1986 the SOM-institute has been carrying out an annual nation-wide survey - the National SOM - in order to identify the Swedish public's habits and attitudes on the topics of society, politics and media. National SOM 2008 is accordingly the twenty-third survey in this series.
The SOM-institute is a collaboration between three departments/institutes at Göteborg University: the Institute for Journalism and Mass Communication, the Department of Political Science, and the Center for Public Sector Research (CEFOS). A number of research projects are involved in the National SOM - most from one of these three institutions, but also external projects are involved.
Since 1998 the survey includes two nation representative samples and uses two different mail questionnaires. One of the questionnaires mainly deals with questions on politics, economy and working life, while the other mainly deals with media, culture and life style. The data collection is carried out in parallel and under identical conditions.
In 2008 one fourth of the questions asked in the two questionnaires are common for both samples, for example questions about media habits, political attitudes, leisure activities, and social background.













The questionnaire on politics includes ten different subject fields: news and media; politics, society and democracy; radio and televisiont; Sweden's relations to the surrounding world; society and public service; environment and energy; knowledge and society; activities, interests, and values; work life; and background questions. The media questionnaire is divided into eight subject fields: news and papers; politics, society and democracy; radio and television; media technology, internet and mobile telephony; culture, society and media; interests, activities and values; work life; and background questions.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den tjugotredje undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

Riks-SOM 2008 genomfördes som två undersökningar med två representativa urval och två olika formulär, där datainsamlingarna genomfördes parallellt och under identiska förhållanden. De båda formulären skiljer sig något åt i det att tyngdpunkten i det ena formuläret ligger på politik och samhälle, medan det andra har en tonvikt på frågor om medier, kultur och livsstil. En knapp fjärdedel av frågorna är gemensamma för de båda frågeformulären och kan därmed analyseras med dubbla urvalsstorleken som grund. Det rör sig dels om SOM-undersökningens grundfrågor om politik och medier samt en stor mängd livsstils- och bakgrundsfrågor, dels om frågor som syftar till att belysa frågeställningar som fordrar ett större urval av svarspersoner för statistiskt säkerställda analyser.

Politikerformuläret (Riks-1) innehåller tio olika frågeområden: nyheter och medier; politik, samhälle och demokrati; radio och tv; Sveriges förhållande till omvärlden; samhälle och service; miljö och energi; kunskap och samhälle; aktiviteter, intressen och värderingar; arbetsliv; samt bakgrundsfrågor. Medieformuläret (Riks-2) tar upp åtta frågeområden: nyheter och tidningar; politik, samhälle och demokrati; radio och tv; medieteknik, internet och mobiltelefoni; kultur, samhälle och medier; intressen, aktiviteter och värderingar; arbetsliv; samt bakgrundsfrågor.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 2008
Riks-SOM 2008
Keywords: mass media; massmedia; population migration; migration; participation; deltagande; environment; miljö; culture; kultur; health; hälsa; environmental degradation; miljöförstörelse; trust; förtroende; quality of life; livskvalitet; european union; europeiska unionen; political interest; politiskt intresse; local government services; kommunal service; nuclear energy; kärnkraft; newspaper readership; tidnings läsekrets; membership; medlemskap; dissemination of information; informationsspridning; trade union membership; medlemskap i fackförening; medical care; sjukvård; radio stations; radiostationer; television channels; tv-kanaler; television advertising; tv-reklam; news; nyheter; television news; tv-nyheter; television programmes; tv-program; theatre attendance; teaterbesök; energy policy; energipolitik; political allegiance; politisk anhängare; television viewing; tv-tittande; globalization; globalisering; education; utbildning; rural population; landsbygdsbefolkning; internet; internet; audio and video equipment; ljud- och videoutrustning; democracy; demokrati; internal politics; inrikespolitik; political parties; politiska partier; political leaders; politiska ledare; households; hushåll; leisure time activities; fritidsaktiviteter; interest (cognitive processes); intresse (kognitiva processer); radio listening; radiolyssnande; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Cultural activities and participation; Kulturaktiviteter och deltagande; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap